EFEKTIVITAS PENGGUNAAN E-BOOK MEMBACA BERBASIS PENDEKATAN KONTEKSTUAL TERHADAP SIKAP PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Rahayu, Dewi Puji; Karlina Wong Lieung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to measure the effectiveness of reading e-books based on a contextual approach to the environmental care attitude of fourth grade elementary school students. This study is a quantitative study. The design of this study is a one group pretest-posttest design. Thus, it can be known more accurately, because it can be compared with being held before being treated. This study was conducted in SD Advent, SD YPK Kuprik and SD YPPK St. Fransiskus Xaverius 2 Merauke. Data collection techniques include tests, observations and documentation. The tests conducted include pretests and posttests. Quantitative data are pretest, posttest and N-gain scores, to determine how effective the application of local wisdom-based teaching materials is by looking at N-gain. The results of the study also showed that the pretest results of students' environmental awareness attitudes without using contextual approach-based reading teaching materials obtained a percentage of 47.25% with a category that was starting to be seen. The posttest results showed an increase in students' environmental awareness attitudes. Students' environmental awareness attitudes at the time of the posttest obtained a percentage of 82.42% with a category that had become a culture.